Roughening liquid for roughening surface of reverse copper foil and preparation method of reverse copper foil
By adding imidazole ionic liquid to the electrolytic mother liquid as additives, the coarse shape of the nano -level "needle -shaped polyononia" is formed, which solves the problem of high contour of copper foil. Demand of high -frequency and high -speed PCB.
Patent Information
- Application Number
- CN202411553190.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, while ensuring the peel resistance strength, the contour of the inverted copper foil is still high, which cannot meet the application needs of high-frequency and high-speed PCBs.
By adding imidazole ionic liquid to the electrolytic mother liquid as additives, the height and adjustable yin and yang ion structure is used to form a blocking layer and promotes the surface of the copper foil surface Reduce roughness.
In the case of ensuring higher anti -peeling strength, the low roughness of the surface of the copper foil to meet the application needs of high -frequency and high -speed PCB, which is specifically manifested as the roughness of the copper foil RZ ≤ 1.435Mm, the anti -peeling strength ≥0.98 N/mm.
Smart Images

Figure CN119372726A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytic copper foil, and in particular to a roughening liquid for roughening the surface of a reverse copper foil and a method for preparing the reverse copper foil. Background Art
[0002] Copper foil, as an indispensable "connecting bridge" for electronic components, is not only the cornerstone of core materials such as lithium-ion batteries (LIBs), copper-clad laminates (CCLs), and printed circuit boards (PCBs), but is also widely used in many key fields such as energy drive, electronic circuit design, and communication engineering. With the leapfrog progress of science and technology, electronic products are moving towards the goal of extreme lightness, high efficiency, and excellent performance. As a key material in the architecture of electronic information products, the importance of copper foil is becoming more and more significant. Especially in high-tech fields such as 5G communications, precision smart chips, cutting-edge integrated circuits, and new energy batteries that lead the future, copper foil plays an indispensable and vital role, driving these industries to a higher level of development.
[0003] During high-frequency and high-speed signal transmission, the current gathers significantly on the conductive surface, and the closer to the center of the conductor, the less dense it is. This phenomenon is called the "skin effect." Given the significant impact of the skin effect on signal transmission, if conventional copper foil is still used for high-frequency signal transmission on PCB, the skin effect will intensify as the signal frequency increases, which will lead to more serious signal "distortion" problems. To solve this problem, low-roughness copper foil is usually used, but lower roughness will result in poor bonding between the copper foil and the resin.
[0004] Traditional electrolytic copper foil has two parts: a smooth surface and a rough surface. Generally, when used in circuit boards, the rough surface is connected to the resin to generate tension, so that the resin and copper foil have a strong bonding force. Since the roughness of the rough surface is deeper, if the rough surface is made on the surface of the circuit board, the uniform rough surface can be directly attached to the dry film, and good bonding can be achieved without too much pre-treatment. Therefore, in order to optimize the manufacturing process and improve the bonding quality, attempts are made to reverse the rough surface of the copper foil and perform additional treatment on the smooth surface to strengthen the bonding. As a result, reverse copper foil (RTF) with roughened surface of the electrolytic copper foil came into being. However, although the electrolytic copper foil obtained by the existing electrolytic copper foil surface treatment process can improve its peeling strength, its contour is relatively high, and the surface roughness R of the bonding surface that serves as the bonding interface with the insulating layer forming material is relatively high. Z All>2.0μm.
[0005] A Chinese patent with authorization announcement number CN115466994B, which was authorized on May 16, 2023, discloses a production process for ultra-low profile reverse copper foil, which includes the following steps in order: pickling, roughening, curing, anti-oxidation, silane and drying. By adding molybdenum ions, vanadium ions and manganese ions with a concentration ratio of 0.1-0.5:0.1-0.5:0.8-2.5 to the roughening liquid during the roughening treatment, the structure of the roughening layer is significantly improved, and a large number of tiny "dendritic" crystals are formed on the surface of the copper foil. The reverse copper foil prepared has a significantly reduced profile while ensuring a high peel strength. The roughened surface Rz of the prepared reverse copper foil is ≤1.5μm, and the peel strength is ≥1.2N / mm.
[0006] However, the reverse copper foil prepared by the above method still has a high profile while ensuring the peeling strength. Summary of the invention
[0007] The purpose of the present invention is to provide a roughening solution for reverse copper foil surface roughening, so as to solve the problem of high profile degree in the prior art while ensuring the anti-peeling strength.
[0008] The second object of the present invention is to provide a method for preparing a reverse copper foil to solve the problem of high profile in the prior art while ensuring the anti-peeling strength.
[0009] In order to solve the above technical problems, the technical solution of the roughening liquid for reverse copper foil surface roughening of the present invention is: A roughening solution for reverse copper foil surface roughening, composed of an electrolytic mother solution and an additive, wherein the electrolytic mother solution includes CuSO4 and H2SO4, and the additive includes an imidazole ionic liquid, wherein the imidazole ionic liquid is selected from one or more of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, and 1-butyl-3-methylimidazole hydrogen sulfate, and the mass concentration of the additive in the roughening solution is 10-90 mg / L.
[0010] The present invention is an improvement on the prior art, and provides a roughening liquid for roughening the surface of reverse copper foil. By adding an imidazole ionic liquid additive to the electrolytic mother liquid, utilizing the highly adjustable anionic and cationic structure of the imidazole ionic liquid, and selecting a specific type of imidazole ionic liquid additive and its composition, an ionic liquid with a specific function is designed, and the barrier layer is formed on the smooth surface of the electrolytic copper foil through complex adsorption, thereby promoting the formation of a tiny nano-scale "needle-shaped polyhedron" roughening morphology on the surface of the copper foil, thereby increasing the specific surface area of the smooth surface of the electrolytic copper foil, and achieving low roughness on the surface of the copper foil while ensuring high peel strength. The roughening liquid additive provided by the present invention can produce a reverse copper foil with a roughness Rz≤1.435µm and a peel strength≥0.98 N / mm, which can meet the application requirements of high-frequency and high-speed PCBs.
[0011] In order to further reduce the roughness of the copper foil and improve the peel strength, preferably, when the imidazole ionic liquid includes 1-hydroxyethyl-3-methylimidazole chloride and 1-(4-mercaptobutyl)-3-methylimidazole bromide, the mass ratio of 1-hydroxyethyl-3-methylimidazole chloride and 1-(4-mercaptobutyl)-3-methylimidazole bromide is (1-1.5): (3-3.5). Using the roughening liquid, the roughness Rz of the reverse copper foil prepared is ≤1.135µm, and the peel strength is ≥1.19 N / mm.
[0012] In order to further reduce the roughness of the copper foil and improve the peel strength, preferably, the imidazole ionic liquid is composed of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, and 1-butyl-3-methylimidazole hydrogen sulfate, and the mass ratio of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, and 1-butyl-3-methylimidazole hydrogen sulfate is (1~1.5): (3~3.5): (1~1.5). The roughening liquid is used to obtain a reverse copper foil with a roughness Rz≤1.062µm and a peel strength ≥1.26 N / mm.
[0013] In order to further reduce the roughness of the copper foil and improve the peeling strength, preferably, the additive includes an inorganic salt, and the inorganic salt is selected from one or more of tungstate, molybdate and manganate.
[0014] In order to further reduce the roughness of the copper foil and improve the peel strength, preferably, the additive is composed of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, 1-butyl-3-methylimidazole hydrogen sulfate and tungstate, and the mass ratio of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, 1-butyl-3-methylimidazole hydrogen sulfate and tungstate is (1~1.5): (3~3.5): (1~1.5): (4~4.5). The roughening solution is used to obtain a reverse copper foil with a roughness Rz≤0.918µm and a peel strength≥1.32 N / mm.
[0015] In order to further improve the deposition efficiency of copper ions on the surface of the copper foil, preferably, the mass concentrations of CuSO4 and H2SO4 in the roughening solution are 10-20 g / L and 180-210 g / L, respectively.
[0016] The technical solution of the reverse copper foil preparation method of the present invention is: A method for preparing reverse copper foil comprises the following steps: using the electrolytic copper foil as a cathode and roughening the smooth surface of the electrolytic copper foil in the roughening solution.
[0017] The reverse copper foil preparation method provided by the present invention roughens the smooth surface of the electrolytic copper foil by adding an additive to the roughening liquid, so that the smooth surface of the copper foil forms a "needle-shaped polyhedron" roughening morphology, thereby increasing the specific surface area of the smooth surface of the electrolytic copper foil, and achieving low roughness of the copper foil surface while ensuring the anti-peel strength.
[0018] In order to further improve the roughening efficiency, preferably, the current density during the roughening treatment is 20-30 A / dm 2 , the temperature is 20~30℃.
[0019] In order to further improve the peel strength, preferably, the roughening treatment is followed by curing, anti-oxidation, silane coupling and drying. The roughening treatment provides more growth sites for the copper foil surface curing, and the copper is rapidly electrodeposited on the copper foil surface by curing to prevent the "needle-shaped polyhedron" crystal layer formed by the roughening from falling off, and the surface roughness is increased to further improve the bonding force between the copper foil and the substrate, and the peel strength of the copper foil on the copper clad laminate is improved. An anti-oxidation film is formed on the surface of the copper foil by anti-oxidation, and the corrosion resistance and anti-oxidation performance of the copper foil are improved. The peel strength of the copper foil on the copper clad laminate is further improved by silane coupling. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM morphology image of the smooth surface of the reverse copper foil prepared using the roughening solution of Example 1; Figure 2The 3D profile morphology of the smooth surface of the reverse copper foil prepared by the roughening solution of Example 1; Figure 3 This is an AFM image of the smooth surface of the reverse copper foil prepared using the roughening solution of Example 1. DETAILED DESCRIPTION
[0021] The technical concept of the roughening solution for reverse roughening of the copper foil surface of the present invention is as follows: The existing technology is to achieve specific adsorption of metal ions on the surface of copper foil by regulating the concentration ratio of molybdenum ions, vanadium ions, manganese ions and tungsten ions as additives in the roughening solution, so as to inactivate part of the electrode surface, thereby making copper ions preferentially adsorbed and precipitated on the uncovered surface, resulting in an uneven surface of the copper foil, forming "dendritic" crystals on the surface of the copper foil, increasing the surface roughness, and the obtained reverse copper foil has ultra-low profile on the basis of high peeling strength.
[0022] The present invention introduces a specific type of imidazole ionic liquid into the roughening solution, which is complexed and adsorbed on the smooth surface of the copper foil to form a barrier layer, and promotes the formation of tiny nano-scale "needle-shaped polyhedron" crystals on the surface of the copper foil, thereby increasing the specific surface area of the smooth surface of the electrolytic copper foil, and achieving low roughness on the surface of the copper foil while ensuring the anti-peel strength.
[0023] The reverse copper foil preparation method provided by the present invention refers to the prior art and sequentially performs the following steps: pickling, roughening, curing, anti-oxidation, silane coupling and drying. Specifically, the electrolytic copper foil is pickled to remove grease and an oxide layer on the surface of the copper foil, and then washed with water to remove residual sulfuric acid and impurities on the surface. The electrolytic copper foil is used as a cathode and iridium-plated titanium is used as an anode. Electrolysis is performed in a roughening solution to roughen the smooth surface of the electrolytic copper foil, and then cured, anti-oxidized, silane coupled and dried to obtain the reverse copper foil.
[0024] In a specific embodiment, the electrolytic copper foil is prepared by direct current electrodeposition according to the prior art; specifically, iridium-plated titanium is used as an anode and a titanium plate is used as a cathode, and direct current electrodeposition is performed in an electroplating solution. 2+ The concentration is 90~100 g / L, the sulfuric acid concentration is 100~120 g / L, the electrodeposition temperature is 45~50℃, and the electrodeposition current density is 40~50A / dm 2 .
[0025] In a specific embodiment, the acid solution used for pickling is 10-12 Vol.% sulfuric acid.
[0026] In a specific embodiment, the electrolyte formula used during curing is: Cu 2+40~50 g / L, sulfuric acid 100~150g / L; the curing temperature is 20~30℃, the current density is 20~30 A / dm 2 .
[0027] In a specific embodiment, the electrolyte formula used for anti-oxidation is: Zn 2+ 5~10 g / L, potassium pyrophosphate (K4P2O7) 80~120 g / L; the temperature for anti-oxidation is 40~50℃, and the current density is 5~10 A / dm 2 , pH range is 10~12.
[0028] In a specific embodiment, silane coupling is performed by spraying a silane coupling agent solution on the surface of the electrolytic copper foil; the volume concentration of the silane coupling agent solution is 1.0-2.0%, and the silane coupling agent is dissolved in a mixed solvent formed by ethanol and water (V:V=1-3:1-3), wherein the silane coupling agent is 3-methacryloxypropyltrimethoxysilane (γ-MPT); the temperature during silane coupling is 25-35°C.
[0029] In a specific embodiment, the temperature during drying is 150-180°C.
[0030] The present invention is described in detail below in conjunction with specific examples. The raw materials used in the following examples are all conventional commercial products and are well known to those skilled in the art.
[0031] 1. Specific embodiments of the roughening solution for reverse copper foil surface roughening of the present invention The formula composition of the roughening solution for roughening the surface of the reverse copper foil of the present invention is shown in Table 1. The roughening solution is obtained by adding additives to the electrolytic mother solution, wherein the electrolytic mother solution is prepared from analytical pure copper sulfate, sulfuric acid and water, and the concentration of CuSO4 in the roughening solution is the mass of commercially available analytical pure copper sulfate added to a certain volume of water, and similarly, the concentration of sulfuric acid is the mass of commercially available concentrated sulfuric acid (mass fraction 98%) added to water.
[0032] Table 1 Roughening solution formula
[0033] The roughening solution for roughening the surface of the reverse copper foil in Example 1 is composed of an electrolytic mother solution and an additive, wherein the additive is [EOHMIM]Cl, and the mass concentrations of CuSO4, H2SO4, and [EOHMIM]Cl in the roughening solution are 20 g / L, 180 g / L, and 10 mg / L, respectively.
[0034] The roughening solution for roughening the surface of the reverse copper foil in Example 2 is composed of an electrolytic mother solution and an additive, wherein the additive is [C4MIM-SH]Br, and the mass concentrations of CuSO4, H2SO4, and [C4MIM-SH]Br in the roughening solution are 20 g / L, 180 g / L, and 30 mg / L, respectively.
[0035] The roughening solution for roughening the surface of the reverse copper foil in Example 3 is composed of an electrolytic mother solution and an additive, wherein the additive is [BMIM]HSO4, and the mass concentrations of CuSO4, H2SO4, and [BMIM]HSO4 in the roughening solution are 20 g / L, 180 g / L, and 10 mg / L, respectively.
[0036] The roughening solution for roughening the surface of the reverse copper foil in Example 4 is composed of an electrolytic mother solution and an additive, wherein the additive is composed of [EOHMIM]Cl and [C4MIM-SH]Br, and the mass concentrations of CuSO4, H2SO4, [EOHMIM]Cl and [C4MIM-SH]Br in the roughening solution are 20 g / L, 180 g / L, 10 mg / L and 30 mg / L, respectively.
[0037] The roughening solution for roughening the surface of the reverse copper foil in Example 5 is composed of an electrolytic mother solution and an additive, wherein the additive is composed of [EOHMIM]Cl, [C4MIM-SH]Br and [BMIM]HSO4, and the mass concentrations of CuSO4, H2SO4, [EOHMIM]Cl, [C4MIM-SH]Br and [BMIM]HSO4 in the roughening solution are 20 g / L, 180 g / L, 10 mg / L, 30 mg / L and 10 mg / L, respectively.
[0038] The roughening solution for roughening the surface of the reverse copper foil in Example 6 is composed of an electrolytic mother solution and an additive, wherein the additive is composed of [EOHMIM]Cl, [C4MIM-SH]Br, [BMIM]HSO4 and Na2WO4, and the mass concentrations of CuSO4, H2SO4, [EOHMIM]Cl, [C4MIM-SH]Br, [BMIM]HSO4 and Na2WO4 in the roughening solution are 20 g / L, 180 g / L, 10 mg / L, 30 mg / L, 10 mg / L and 40 mg / L, respectively.
[0039] The roughening solution for roughening the surface of the reverse copper foil in Example 7 is composed of an electrolytic mother solution and an additive, wherein the additive is [EOHMIM]Cl. The mass concentrations of CuSO4, H2SO4, and [EOHMIM]Cl in the roughening solution are 20 g / L, 180 g / L, and 40 mg / L, respectively.
[0040] 2. Specific embodiments of the reverse copper foil preparation method of the present invention Example 8 The method for preparing the reverse copper foil of this embodiment is as follows: (1) Preparation of electrolytic copper foil: Iridium-plated titanium is used as the anode and titanium plate is used as the cathode. Direct current electrodeposition is performed in the electroplating solution. The Cu 2+ The concentration is 90 g / L, the sulfuric acid concentration is 100 g / L, the electrodeposition temperature is 45°C, and the electrodeposition current density is 40 A / dm 2 .
[0041] (2) Pickling: The electrolytic copper foil prepared in step (1) is pickled with 10 vol.% sulfuric acid to remove grease and oxide layer on the surface of the electrolytic copper foil, and then washed with water to remove residual sulfuric acid and impurities on the surface.
[0042] (3) Roughening: The electrolytic copper foil is used as the cathode and the iridium-plated titanium is used as the anode. Electrolysis is performed in the roughening solution of any one of Examples 1 to 7 to roughen the smooth surface of the electrolytic copper foil. The current density during electrolysis is 20 A / dm 2 , the electrolysis temperature is 30℃.
[0043] (4) Curing: After the roughening treatment, the curing treatment is carried out by electrolysis in the electrolyte. The electrolyte formula used during curing is: Cu 2+ 40 g / L, sulfuric acid 120 g / L; the curing temperature is 30°C, the current density is 20 A / dm 2 .
[0044] (5) Anti-oxidation: After curing treatment, the electrolyte is electrolyzed in the electrolyte for anti-oxidation treatment. The electrolyte formula used for anti-oxidation is: Zn 2+ 10 g / L, potassium pyrophosphate (K4P2O7) 100 g / L; the temperature for anti-oxidation is 40°C, and the current density is 10A / dm 2 , pH range is 10~12.
[0045] (6) Silane coupling: After anti-oxidation treatment, 3-methacryloxypropyltrimethoxysilane (γ-MPT) solution is sprayed on the smooth surface of the electrolytic copper foil. The γ-MPT solution is prepared by dissolving γ-MPT in a mixed solvent of ethanol and water in a volume ratio of 1:1. The volume concentration of the γ-MPT solution is 1%, and the spraying temperature is 30°C.
[0046] (7) Drying: After silane coupling, the copper foil is dried at 160°C to obtain a reverse copper foil.
[0047] 3. Comparative Proportion Comparative Example 1 The roughening solution used for roughening the surface of the reverse copper foil in this comparative example is basically the same as that in Example 1, except that no additive is added to the electrolytic mother solution.
[0048] Comparative Example 2 The roughening solution used for roughening the surface of the reverse copper foil in this comparative example is basically the same as that in Example 1, except that the additive added to the electrolytic mother solution is 40 mg / L Na2WO4.
[0049] IV. Experimental Examples Experimental Example 1 In this experimental example, the morphology of the polished surface of the prepared reverse copper foil is characterized. Figure 1-3 The SEM morphology, 3D contour morphology, and AFM images of the smooth surface of the reverse copper foil prepared using the roughening solution of Example 1 are shown respectively. Figure 1-3 It can be seen that a large number of tiny nanoscale "needle-shaped polyhedron" copper nodules grow on the smooth surface of the inverted copper foil, ensuring a low roughness on the surface of the copper foil and greatly increasing the specific surface area of the copper foil.
[0050] Experimental Example 2 In this experimental example, the roughness Rz and peel strength of the prepared reverse copper foil surface were tested. The roughness Rz was tested by a JD-520 roughness meter, and the peel strength was tested by a MK-BL-X-90 degree peel strength tester.
[0051] The specific test method is as follows: 1. Roughness test: Place the copper foil flat on the operating table, then place the roughness instrument probe on the surface of the copper foil, and test the copper foil three times in the horizontal and vertical directions. The average of the six experimental results is taken as the test result of the roughness Rz; 2. Peel strength test: Four test strips with a width of 3.0 mm were cut from the surface of the copper-clad laminate formed by pressing the copper foil and the FR-4 prepreg. The test was conducted at a peeling speed of 50 mm / min and a test angle of 90±5°. The peel strength of each test strip was calculated based on the minimum load displayed by the instrument. The average of the four experimental results was taken as the peel strength test result. The test results are shown in Table 2.
[0052] Table 2 Roughness Rz and peel strength test results of the reverse copper foil smooth surface
[0053] It can be seen from Table 2 that, compared with the roughening solution without adding additives (Comparative Example 1), the roughening solution provided by the present invention improves the surface roughness, but greatly improves the peeling strength between the smooth surface and the resin; compared with the roughening solution using a single sodium tungstate additive (Comparative Example 2), the roughening solution provided by the present invention can significantly improve the peeling strength between the reverse copper foil and the resin, while reducing the profile of the smooth surface.
[0054] The roughness Rz of the smooth surface of the reverse copper foil prepared by the roughening liquid provided by the present invention is ≤1.435µm, and the peel strength Ps is ≥0.98 N / mm, indicating that the addition of imidazole ionic liquid additives to the roughening liquid promotes the formation of tiny nano-scale "needle-shaped polyhedron" crystals on the surface of the copper foil, which can increase the specific surface area of the smooth surface of the electrolytic copper foil, thereby ensuring high peel strength while achieving low roughness on the surface of the copper foil.
[0055] At the same time, the addition of multi-component additives (Examples 4-6) to the roughening liquid exhibits lower roughness and higher peel strength than single additives (Examples 1-3, Example 7); in particular, compared with Example 7, Example 4 has lower roughness and higher tensile strength, indicating that multi-component additives have a synergistic effect compared with single components; the addition of a ternary component additive (Example 5) has lower roughness and higher peel strength than the two-component (Example 4), and similarly, the four-component additive (Example 6) exhibits the same properties as the ternary component (Example 5).
[0056] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A roughening solution for reverse copper foil surface roughening, characterized in that: The invention is composed of an electrolytic mother solution and an additive, wherein the electrolytic mother solution includes CuSO4 and H2SO4, and the additive includes an imidazole ionic liquid, wherein the imidazole ionic liquid is selected from one or more of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, and 1-butyl-3-methylimidazole hydrogen sulfate, and the mass concentration of the additive in the roughening solution is 10-90 mg / L.
2. The roughening solution for reverse copper foil surface roughening according to claim 1, characterized in that: When the imidazolium ionic liquid includes 1-hydroxyethyl-3-methylimidazole chloride and 1-(4-mercaptobutyl)-3-methylimidazole bromide, the mass ratio of 1-hydroxyethyl-3-methylimidazole chloride and 1-(4-mercaptobutyl)-3-methylimidazole bromide is (1~1.5):(3~3.5).
3. The roughening solution for reverse copper foil surface roughening according to claim 1, characterized in that: The imidazole ionic liquid is composed of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, and 1-butyl-3-methylimidazole hydrogen sulfate, and the mass ratio of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, and 1-butyl-3-methylimidazole hydrogen sulfate is (1-1.5): (3-3.5): (1-1.5).
4. The roughening solution for reverse copper foil surface roughening according to any one of claims 1 to 3, characterized in that: The additive comprises an inorganic salt, and the inorganic salt is selected from one or more of tungstate, molybdate and manganate.
5. The roughening solution for reverse copper foil surface roughening according to claim 1, characterized in that: The additive consists of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, 1-butyl-3-methylimidazole hydrogen sulfate and tungstate, and the mass ratio of 1-hydroxyethyl-3-methylimidazole chloride, 1-(4-mercaptobutyl)-3-methylimidazole bromide, 1-butyl-3-methylimidazole hydrogen sulfate and tungstate is (1-1.5): (3-3.5): (1-1.5): (4-4.5).
6. The roughening solution for reverse copper foil surface roughening according to claim 1, characterized in that: The mass concentrations of CuSO4 and H2SO4 in the coarsening solution are 10~20g / L and 180~210g / L, respectively.
7. A method for preparing a reverse copper foil, characterized in that: The method comprises the following steps: using the electrolytic copper foil as a cathode, and roughening the light surface of the electrolytic copper foil in the roughening solution described in any one of claims 1 to 6.
8. The method for preparing a reverse copper foil according to claim 7, characterized in that: The current density during roughening treatment is 20~30 A / dm 2 , the temperature is 20~30℃.
9. The method for preparing a reverse copper foil according to claim 7, characterized in that: After the roughening treatment, it is cured, anti-oxidized, silane coupled and dried.
Citation Information
Patent Citations
A manufacturing process for ultra-low profile reverse copper foil
CN115466994B